The management of impacted maxillary central incisor in growing age period patient (Case Report) - Habar, Eddy H. (Hasanuddin University, 2020)
Objectives: This article discusses case reports of impacted maxillary central incisor with orthodontic treatment approaches and minor surgical exposure measures.Methods: A 12-year-old male patient presents with impacted maxillary central incisor, complaining of the appearance and aesthetics of his face. Objective examination showed edentulous in region 21 and the area narrowed. Results: An orthodontic treatment is performed to open the space, followed by surgical exposure to attach a button for impacted tooth withdrawalConclusion: Maximum results are obtained with interdisciplinary treatment, in this case minor surgical exposure by an oral surgeon.